Estudio del software “STAR” de la Corporación CNEL para la medición de energía eléctrica con radiofrecuencia en la Parroquia Clemente Baquerizo - Sector Urbano Marginal Sol Brisa 1 - Zapata Villacis, Milton Alexander (2019)
This case study was developed in order to analyze the advantages, disadvantages and characteristics of the software of the radiofrequency meters of the STAR brand of the National Electricity Corporation - Public Company and its effects on the application of this system. The parameters of the descriptive investigation (description of perceived general facts) and the deductive method (obtaining causes and consequences of the use of the system or software of radiofrequency meters) were implemented. From the analysis of the STAR computer system it was possible to obtain as a result that it has advantages such as the improvement of the security related to the reading of electric power consumption, because the information is stored directly in the system